Quantitative analysis of local fine structure on diffusion of point defects in passive film on Ti. (10th August 2019) - Wang, Lu; Yu, Hongying; Wang, Shaoyang; Chen, Bao; Wang, Yuhang; Fan, Wenqiang; Sun, Dongbai
Abstract: The diffusion of point defects in passivation determines all physico-electrochemical processes in materials corrosion and protection. In this study, a multiscale quantitative methodology was developed to reveal the diffusivity of oxygen vacancies on titanium surface (～5.0 nm thickness) in 1.0 M H2 SO4 solution based on X-ray absorption fine structure (XAFS), combining with electrochemical impedance spectroscopy (EIS) and Mott-Schottky. EIS equivalent circuit exhibits that the high electronic field across passive film is 1.06 × 10 6 V cm –1 . Mott-Schottky space charge capacitance indicates n-type semiconducting film with the donor density of ～10 21 cm –3 . Three important structure parameters have been firstly proposed from XAFS theoretical calculation at Ti K-edge to quantitatively describe the point defects transport between metal/film/solution interfaces. The half-jump distance equals half Ti–Ti distance subtly changing with oxidation potentials. The coordination coefficient is defined as the probability of activation jump from Ti–O coordination. And the Debye-Waller factor of structure disorder is related to the donor density of Mott-Schottky. Overall, the diffusivity of oxygen vacancies is in the range of (1.84–4.71) × 10 –17 cm 2 s –1 under the electric field, which determines the interfacial equilibrium of passivation and dissolution during potentiodynamic polarization. And the activation energy for motion has a minimum of 0.89 eV at 1.5 V. This multiscale quantitative methodology predicts well the potential dependent steady-state in the corrosive system. Graphical abstract: Image 10485 Highlights: XAFS was innovatively used for quantitative passivation kinetics analysis. EIS and Mott-Schottky were related to local fine structure to estimate diffusion. Three atomic structure parameters were firstly proposed for point defect transport. Transport of oxygen vacancies at metal/film/solution interfaces was constructed. The diffusivity of oxygen vacancies was more accurately calculated.